Cystatin C in the diagnostics of acute kidney injury after heart transplantation - A. G. Strokov; Ya. L. Poz; V. N. Poptsov; A. O. Shevchenko; N. P. Shmerko (Вестник трансплантологии и искусственных органов)
Aim. To examine the assumption that significant concentrations of cystatin C in urine are the manifestation of the tubular necrosis and, respectively, the severity of kidney damage after heart transplantation (HTx).Materials and methods. In this study we evaluated 33 heart recipients (6 women and 27 men, aged from 24 to 68 years old) who had risk factors of acute kidney injury: serum creatinine level >113 μmol/l and/or mechanical circulatory support requirement (20 patients, in 14 cases before HTx). Cystatin C concentration in serum and in urine was measured by DyaSis particle-enhanced immunoturbidimetric assay test «Cystatin C FS».Results. Recipients were divided into two groups according to the levels of cystatinuria. In the group with the significant (more than 0.18 mg/l) urinary cystatin C concentrations the requirement of renal replacement therapy (RRT) was 2.5-fold higher, and the mean duration of RRT was more than 10-fold longer. In 2 patients with the significant cystatinuria acute kidney injury (AKI) has transformed into end-stage renal disease (ESRD).Conclusion. Due to data obtained we may suppose that significant concentrations of cystatin C in urine are the marker of the tubular necrosis with the prolonged RRT requirement. Further studies are needed to justify this relationship.